Iron Acquisition Strategies of Vibrio anguillarum - Li, Yingjie; Ma, Qingjun (Frontiers in Cellular and Infection Microbiology, 2017)
The hemorrhagic septicemic disease vibriosis caused by Vibrio anguillarum shows noticeable similarities to invasive septicemia in humans, and in this case, the V. anguillarum–host system has the potential to serve as a model for understanding native eukaryotic host–pathogen interactions. Iron acquisition, as a fierce battle occurring between pathogenic V. anguillarum and the fish host, is a pivotal step for virulence. In this article, advances in defining the roles of iron uptake pathways in growth and virulence of V. anguillarum have been summarized, divided into five aspects, including siderophore biosynthesis and secretion, iron uptake, iron release, and regulation of iron uptake. Understanding the molecular mechanisms of iron acquisition will have important implications for the pathogenicity of this organism.